Adrenal cortex tissue homeostasis and zonation: A WNT perspective. (15th June 2015) - Drelon, Coralie; Berthon, Annabel; Mathieu, Mickael; Martinez, Antoine; Val, Pierre
Highlights: Adrenal cortex renewal occurs through centripetal cell displacement and lineage conversion from glomerulosa to fasciculata. WNT signalling establishes glomerulosa identity and represses fasciculata identity. WNT signalling has to repress to allow lineage conversion. PKA signalling may be involved in this repression. Abstract: The adrenal cortex plays essential roles in the control of sodium and water homeostasis, stress response, inflammation and metabolism, through secretion of glucocorticoids and mineralocorticoids. Coordinated production of these hormones relies on functional zonation of the cortex, characterised by expression of Cyp11b2 under the control of angiotensin II and plasma potassium level in zona glomerulosa (ZG) and Cyp11b1 under the control of ACTH in zona fasciculata (ZF). The mechanisms involved in the establishment of functional zonation and its maintenance during centripetal cortex cell renewal are still poorly understood. Here, we hypothesise that the hormonal and signalling pathways that control adrenal cortex function are also involved in cortical zonation. In particular, we summarise evidence on the role of WNT/β-catenin signalling in ZG differentiation and how tight control of its activity is required to shape the adult cortex. In this context, we discuss the potential role of known WNT regulators and the possibility of a reciprocal cross-talk between PKA and WNT signalling.